2022
DOI: 10.30935/conmaths/12340
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Classroom Management and Mastery-Oriented Instructions on Relationship Between Pedagogical Content Knowledge and Mathematics Achievement

Abstract: Despite multiple studies in the past, seeking to assess the determinants of students' achievement in mathematics, less attention has been paid to the simultaneous role of classroom management (CM), mastery-oriented instructions, and teacher pedagogical content knowledge (PCK). This study, therefore, looked at the mediation effects of mastery-oriented instructions and CM in the relationship between teacher PCK and students' mathematics achievement. The study was a survey and quantitative. A simple random sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Pan and Franklin (2011) found that classroom management and motivation influenced students' mathematics achievement. Owusu et al (2022) also identify that the relationship between classroom management and mathematics achievement was positive and significant. Classroom management, student motivation, and self-determination were identified by Irfan et al (2020) as determinants of mathematics achievement.…”
Section: Introductionmentioning
confidence: 85%
“…Pan and Franklin (2011) found that classroom management and motivation influenced students' mathematics achievement. Owusu et al (2022) also identify that the relationship between classroom management and mathematics achievement was positive and significant. Classroom management, student motivation, and self-determination were identified by Irfan et al (2020) as determinants of mathematics achievement.…”
Section: Introductionmentioning
confidence: 85%
“…Some studies have shown that students' mastery orientation has an influence on their interest, motivation, and academic achievement in mathematics (Furner & Gonzalez-DeHass, 2011;Owusu et al, 2022). The construct consists of four statements that capture students' perceptions regarding performance-related behaviors, including the willingness to make mistakes and the desire to obtain correct answers.…”
Section: Student Mastery (Vs Performance) Orientationmentioning
confidence: 99%